ANALYTICAL CONCLUSION ON FOREIGN RESEARCH ON THE CREATION OF MATHEMATICAL MODELING - Dilafruz Nurjabova (ZAMONAVIY TA’LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2026)
Abstract. This article presents an analytical review of foreign studies devoted to the development and application of mathematical modeling in scientific research. The analysis shows that mathematical modeling is widely used as an effective method for describing complex processes, forecasting system behavior, and optimizing decision-making in various fields, including economics, education, engineering, medicine, and environmental sciences. Foreign researchers emphasize that the effectiveness of mathematical models depends on the correct selection of variables, the accuracy of initial data, and the validity of assumptions used in model construction. The study also highlights the importance of combining mathematical modeling with computer technologies, simulation methods, and data analysis tools. As a result, mathematical modeling is considered not only as a theoretical research method but also as a practical instrument for solving applied problems. The review concludes that international experience can serve as a methodological basis for improving mathematical modeling approaches in modern scientific research.